Empowerment of Farmer Group Based On Rice Farming In Ponorogo District - Mardan; Ahsin Daroini; Abu Talhah (Faculty of Agriculture, Merdeka University Surabaya, 2019)
Empowerment is an effort to meet the needs of individuals, groups and the wider community so that they have the ability to make choices and control their environment in order to fulfill their desires, including their accessibility to resources related to their work in social activities. The purpose of this study are: a. determining the empowerment strategy of Rice Crop-based Gafarmer-group in Ponorogo District. b. analyzing the most suitable strategy applied to the empowerment of rice-based Gafarmer-group in Ponorogo district. This study uses a qualitative approach. Methods Analysis of the data in this study is an analysis sequence that constructs research conclusions that are ordered in order: IFE Matrix, EFE Matrix, SWOT and QSPM. The research results some alternatives sequence of rice-based Gafarmer-group’s empowerment strategies in Ponorogo district: [a] based on the SWOT matrix: (1) Strategies SO (Strength-Opportunity). Improving the strategy of managing agricultural land to accelerate the processing of extensive land using agricultural processing machines. (2) Strategies WO (Weaks-Oppurtunities). Rejuvenation of farmers by regenerating younger farmers by conducting training so that farmers are more competent. (3) Strategies ST (Strength-Threats). Improved strategy for controlling natural disaster landslides to control the amount of damage to agricultural land. (4) Strategies WT (Weaks-Threats). Improving infrastructure to facilitate farmer’s access. Based on QSPM matrix: The most suitable strategy to be applied in the empowerment farmer-groups of rice-based in Ponorogo District can be seen based on the analysis of the choice of strategies for the: 1). Rejuvenation of farmers by regenerating younger farmers by conducting training so that farmers are more competent. 2). Increased experience of farmer groups with training held by farmer-groups.